Producing and Using Organic NPK Fertilizer From Agricultural and Household Waste by a Farmer Group in Sleman, Yogyakarta - Sudaryatno, Sudaryatno; Prasetya, Agus; Sulaiman, Muhammad; Sartika, Heni Wahyu; Santoso, Dian Hudawan; Bato, Marjan; Fadliyah, Nurul; Maliga, Iga; Kisnanto, Indro (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
The agricultural industry, including the cultivation of paddy and vegetables, plays a crucial role in the economy of Padukuhan Dukuh and serves as its residents' primary source of income. Nevertheless, farmers have expressed that the challenge of acquiring subsidized fertilizers from the government substantially hinders the agricultural process. Compound fertilizer, often known as NPK fertilizer, is a specific chemical fertilizer frequently used by farmers to enhance soil fertility rapidly. This community service program aims to spread awareness about using alternative fertilizers (such as compost and liquid organic NPK) to minimize the adverse effects of fertilization on the environment. Additionally, the program seeks to promote the conversion of agricultural and household waste into organic fertilizers. The service activity took place from September 10 to October 14, 2023. Padukuhan Dukuh is the location where the production of alternative organic fertilizers using agricultural and home waste takes place. This service aims to offer support to the members of the